Coronary atherosclerotic plaque progression: contributing factors in statin-treated patients. (1st December 2020) - Clark, Donald; Puri, Rishi; Nissen, Steven E.
ABSTRACT: Introduction : Coronary atheroma progression correlates with adverse cardiovascular events among individuals with coronary artery disease. Atherosclerosis imaging, including coronary intravascular ultrasound (IVUS), has provided novel insights into the biologic contributors to atheroma progression or regression, improving the efficiency of drug development by identifying therapies most likely to succeed in clinical outcomes trials. Areas covered : Despite widespread use of statins, residual risk for adverse events is high among individuals with cardiovascular disease receiving optimal medical therapy. This review outlines current studies, including patient-level analyses of large randomized clinical trials, demonstrating several factors that associate with coronary plaque progression in the context of statin therapies. Expert opinion : Atherosclerotic plaque remains a fundamental substrate underlying the occurrence of ischemic events in the current era of cardiovascular care. Understanding pathobiologic contributors to atherosclerosis, targeting treatment pathways, generating high-quality data, and implementing evidence into clinical practice are necessary to improve outcomes among patients with atherosclerotic disease.